A Genetic Screen Reveals that Synthesis of 1,4-Dihydroxy-2-Naphthoate (DHNA), but Not Full-Length Menaquinone, Is Required for Listeria monocytogenes Cytosolic Survival - Grischa Y. Chen (American Society for Microbiology, 2017)
ABSTRACT Through unknown mechanisms, the host cytosol restricts bacterial colonization; therefore, only professional cytosolic pathogens are adapted to colonize this host environment. Listeria monocytogenes is a Gram-positive intracellular pathogen that is highly adapted to colonize the cytosol of both phagocytic and nonphagocytic cells. To identify L. monocytogenes determinants of cytosolic survival, we designed and executed a novel screen to isolate L. monocytogenes mutants with cytosolic survival defects. Multiple mutants identified in the screen were defective for synthesis of menaquinone (MK), an essential molecule in the electron transport chain. Analysis of an extensive set of MK biosynthesis and respiratory chain mutants revealed that cellular respiration was not required for cytosolic survival of L. monocytogenes but that, instead, synthesis of 1,4-dihydroxy-2-naphthoate (DHNA), an MK biosynthesis intermediate, was essential. Recent discoveries showed that modulation of the central metabolism of both host and pathogen can influence the outcome of host-pathogen interactions. Our results identify a potentially novel function of the MK biosynthetic intermediate DHNA and specifically highlight how L. monocytogenes metabolic adaptations promote cytosolic survival and evasion of host immunity. IMPORTANCE Cytosolic bacterial pathogens, such as Listeria monocytogenes and Francisella tularensis, are exquisitely evolved to colonize the host cytosol in a variety of cell types. Establishing an intracellular niche shields these pathogens from effectors of humoral immunity, grants access to host nutrients, and is essential for pathogenesis. Through yet-to-be-defined mechanisms, the host cytosol restricts replication of non-cytosol-adapted bacteria, likely through a combination of cell autonomous defenses (CADs) and nutritional immunity. Utilizing a novel genetic screen, we identified determinants of L. monocytogenes cytosolic survival and virulence and identified a role for the synthesis of the menaquinone precursor 1,4-dihydroxy-2-naphthoate (DHNA) in cytosolic survival. Together, these data begin to elucidate adaptations that allow cytosolic pathogens to survive in their intracellular niches.